2019
DOI: 10.1093/ofid/ofz148
|View full text |Cite
|
Sign up to set email alerts
|

Housing Instability Results in Increased Acute Care Utilization in an Urban HIV Clinic Cohort

Abstract: Background People living with HIV (PLWH) who experience homelessness and unstable housing (HUH) often have fragmented health care. Research that incorporates granular assessments of housing status and primary care visit adherence to understand patterns of acute care utilization can help pinpoint areas for intervention. Methods We collected self-reported living situation, categorized as stable (rent/own, hotel/single room occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Both substandard and lack of housing are associated with a panoply of health conditions [35], and communities of colour in the US are more likely to experience poorer housing conditions [36]. A San Francisco‐based cross‐sectional study of 1222 people living with HIV found a direct relationship between high viral load and being homeless [37]. Another study reported that people diagnosed with HIV while homeless have a 27‐fold greater odds of death compared to those diagnosed with access to shelter [38].…”
Section: Discussionmentioning
confidence: 99%
“…Both substandard and lack of housing are associated with a panoply of health conditions [35], and communities of colour in the US are more likely to experience poorer housing conditions [36]. A San Francisco‐based cross‐sectional study of 1222 people living with HIV found a direct relationship between high viral load and being homeless [37]. Another study reported that people diagnosed with HIV while homeless have a 27‐fold greater odds of death compared to those diagnosed with access to shelter [38].…”
Section: Discussionmentioning
confidence: 99%
“…Two US studies from 2012 and 2014 found that being employed was associated with a reduced hospitalisation rate [ 14 , 19 ], while two other studies found no association with monthly income, [ 10 , 12 ] and results relating to education were inconsistent in PLHIV [ 10 , 12 , 14 , 19 ]. A US study found an association between unstable housing or homelessness and increased rate of hospitalisation in PLHIV [29] . To our knowledge, there are no recent European studies investigating the association of socioeconomic factors with hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals experiencing housing instability have been shown to have higher rates of ED and acute care utilization than stably housed individuals. 27,28 Unaffordable housing has also been associated with increased odds of hypertension and cost-related healthcare non-adherence, as well as worse self-rated health compared to controls using propensity score analyses. 29 In our study, 28% of ED patients reported having unstable housing, suggesting that the ED may offer significant opportunities for homelessness prevention through linkage to legal and social services.…”
Section: Housing Instabilitymentioning
confidence: 99%